2014
DOI: 10.1002/anie.201400626
|View full text |Cite
|
Sign up to set email alerts
|

A New Structural Motif for an Enantiomerically Pure Metallosupramolecular Pd4L8 Aggregate by Anion Templating

Abstract: An enantiomerically pure BINOL-based bis(3-pyridyl) ligand 1 assembles into a homochiral [Pd4(1)8] complex upon coordination to tetravalent Pd(II) ions. The formation of this aggregate is templated by two tetrafluoroborate counterions that are encapsulated in two peripheral cavities. The resulting structure is a new structural motif for this kind of metallosupramolecular assemblies that arranges the palladium ions in a distorted tetrahedral fashion and forces ligand 1 to adopt two different conformations. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 39 publications
1
41
0
5
Order By: Relevance
“…The structures of both C1 and C2 were modelled at the HF/6‐31G(d) level of theory (Figure a), and were found to be very similar. They resemble metallamacrocyclic structures in which two ligands doubly bridge between adjacent Pd centres around the macrocycle, in a crown‐like fashion . Of potential structures of [L 8 Pd 4 ] cages, this particular arrangement is rare, only five examples of assemblies with this structural motif were reported to date .…”
Section: Resultsmentioning
confidence: 58%
“…The structures of both C1 and C2 were modelled at the HF/6‐31G(d) level of theory (Figure a), and were found to be very similar. They resemble metallamacrocyclic structures in which two ligands doubly bridge between adjacent Pd centres around the macrocycle, in a crown‐like fashion . Of potential structures of [L 8 Pd 4 ] cages, this particular arrangement is rare, only five examples of assemblies with this structural motif were reported to date .…”
Section: Resultsmentioning
confidence: 58%
“…1a) are known. In contrast to the multiple binding sites of the multi-3D-cavity cages, there exist single-3D-cavity systems capable of accommodating multiple variety of guests in site-specific manner 28,29 . It is pertinent to note that a variety of 3D-metal−organic frameworks possessing an infinite number of conjoined-cages in their architectures are known 7 .…”
mentioning
confidence: 99%
“…The topology of RuPd resembles that reported by Klein et al wherein the cage structure is constructed such that two ligands doubly bridge adjacent Pd(II) centres in a crown-like fashion, disposing the four palladium ions in a square arrangement. 23 This forms a metallomacrocyclic core to the cage. Among the family of Pd 4 L 8 cages, this specific arrangement is rare with only six examples reported to date.…”
mentioning
confidence: 99%
“…Among the family of Pd 4 L 8 cages, this specific arrangement is rare with only six examples reported to date. 9c, [23][24] Indeed, this stoichiometry is only possible when the angle between the coordinating 4-pyridyl units is less than 90 o ; the X-ray structure of Ruqpy revealed that the angle between the coordinating 4-pyridyl units of the qpy ligand measures 69 o ( Figure S3). The angle between the coordinating 4pyridyl units of Ruqpy is smaller than that of the previously reported complex [Ir(mesppy)2(qpy)]PF6, which showed a coordinating angle of 78 o .…”
mentioning
confidence: 99%